Translation elongation factor 1-alpha gene as a marker for diagnosing of candidal onychomycosis - Keyvan Pakshir; Forough Farazmand; Farnoush Ghasemi; Hossein Mirhendi; Kamiar Zomorodian; Mahboobeh Kharazi; Ramtin Alborzi pour; Hajar Golestani; Marjan Motamedi (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Culture-based identification methods have been the gold standard for the diagnosis of candidal onychomycosis. Molecular technologies, such as polymerase chain reaction (PCR) assays, can provide an alternative for the rapid detection of Candida species. The present study was conducted to investigate a pan-Candida PCR assay based on the translation elongation factor 1-alpha (TEF-1α) gene for the detection of the most prevalent pathogenic Candida species. Materials and Methods: For the purpose of the study, an optimized pan-Candida PCR primer pair was designed, and the target was amplified and sequenced. The analytical and clinical diagnostic performance of the designed primers was tested using 17 reference strains, 137 nail scrapings suspected of onychomycosis, and 10 healthy nail specimens. Results: The use of the universal pan-Candida primers designed on TEF-1α gene resulted in the successful amplification of a 270-base pair fragment in all Candida species tested, except for C. glabrata, and reacted neither with other fungi nor with E. coli. The sequence difference count matrix showed poor insertion/deletion differences (0-2 nt) among Candida species. Among 137 nail specimens, 35% (n=48), 30.7% (n=42), and 40.1% (n=55) of the samples were found to be positive by direct microscopy, culture, and pan-Candida PCR, respectively. Conclusion: Based on the findings, the PCR-based detection targeting the DNA TEF-1α gene is a rapid and simple procedure for the diagnosis of candidal onychomycosis directly from nail sample.